2021
DOI: 10.1177/03080226211020659
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the process of health in mothers of children with cerebral palsy: Changing “clinical reasoning”

Abstract: Introduction The issue of the health status of mothers of children with disability is one that is beginning to be addressed more fully. This study aimed to explore the process of health in mothers during caregiving of children with cerebral palsy (CP). Method A qualitative research method with a grounded theory approach was used, including purposive and theoretical sampling. A constant comparative analysis method was adopted, and data were gathered from 15 mothers with CP children through interviews. Results T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Mothers believed that they were ultimately responsible for instigating lifestyle changes and accessing the content between coaching sessions, thus highlighting the importance of mothers' volition throughout the programme. Maternal insight and motivation were raised as key issues in a qualitative study about the health experiences of mothers of children with cerebral palsy (Dehghan et al, 2021 ). Dehghan et al concluded that occupational therapists were in a prime position to include mothers and wider family issues within their clinical reasoning to better support families of children with disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mothers believed that they were ultimately responsible for instigating lifestyle changes and accessing the content between coaching sessions, thus highlighting the importance of mothers' volition throughout the programme. Maternal insight and motivation were raised as key issues in a qualitative study about the health experiences of mothers of children with cerebral palsy (Dehghan et al, 2021 ). Dehghan et al concluded that occupational therapists were in a prime position to include mothers and wider family issues within their clinical reasoning to better support families of children with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the recent Royal Commission into Victoria's Mental Health ( 2021 ) highlighted that “parents find it difficult to access services … experience long wait times and stigmatising responses in seeking help for themselves” (p. 12). The occupations of children and their mothers are closely related (Bhopti et al, 2020 ), and mothers have identified that compromising their own health can be a consequence of providing high‐quality care (Davland et al, 2015 ; Dehghan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The literature has revealed that mothers of children with disabilities cannot allocate time to recreational activities and do not have enough time for routine activities of daily living. Dehghan et al [9] stated that women with children with CP neglect their own health needs while seeking ways to minimize the barriers faced by their children. The reasons for this are to constantly take care of the child with a disability and the obligation to substitute for the self-care and ambulation that the child cannot practice [11,25].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the parents of children with a developmental disability are one of the most essential parts of the rehabilitation team. Particularly, mothers have a fundamental role in managing the many factors that affect children's health and reach to therapy services [9].…”
Section: Introductionmentioning
confidence: 99%
“…The shared experiences of other parents helped mothers think positively about the destiny of their child (Cauda-Laufer 2017 ). The social interaction and social structures in these groups provide emotional support to mothers of children with disabilities (Dehghan et al 2022 ).…”
Section: Contextualising This Papermentioning
confidence: 99%